Axiological nihilism according to Adorno and Horkheimer - Estrada Díaz, Juan Antonio (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The lack of objective references leads to subjective reason, with a loss of ends and everything turned into a means, because it is not possible to be based on anything. It is the eclipse of reason; thus, the rise of axiological nihilism and cognitive relativism. The belated pessimism of Horkheimer brings him to look for humanist instances in religion and ethics, both of which can transcend the administered society. Adorno makes the experience of suffering as the starting point of his philosophy, integrating negative dialectics, the Christian perspective on victims and the transcendence of aesthetics.
Keywords: nihilism; axiology; ethics; religion; reason